2016
DOI: 10.1111/eos.12324
|View full text |Cite
|
Sign up to set email alerts
|

Human salivary gland cells express bradykinin receptors that modulate the expression of proinflammatory cytokines

Abstract: Bradykinin is an important peptide modulator that affects the function of neurons and immune cells. However, there is no evidence of the bradykinin receptors and their functions in human salivary glands. Here we have identified and characterized bradykinin receptors on human submandibular gland cells. Both bradykinin B1 and B2 receptors are expressed on human submandibular gland cells, A253 cells, and HSG cells. Bradykinin increased the intracellular Ca concentration ([Ca ] ) in a concentration-dependent manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
(51 reference statements)
0
7
0
1
Order By: Relevance
“…We have studied salivary GPCRs for the past decade. We found that histamine H1 receptor 27 as well as muscarinic receptors causes aquaporin-5 translocation, but that the stimulation of sphingosine-1-phosphate receptor 28 and bradykinin B2 receptor 29 does not affect AQP-5 translocation. Therefore, our current study of salivary secretion by ZnR/GPR39 in human subjects is of significance in salivary translational research.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We have studied salivary GPCRs for the past decade. We found that histamine H1 receptor 27 as well as muscarinic receptors causes aquaporin-5 translocation, but that the stimulation of sphingosine-1-phosphate receptor 28 and bradykinin B2 receptor 29 does not affect AQP-5 translocation. Therefore, our current study of salivary secretion by ZnR/GPR39 in human subjects is of significance in salivary translational research.…”
Section: Discussionmentioning
confidence: 70%
“…The fluorescent Ca 2+ indicator Fura-2 was used to determine [Ca 2+ ] i level, as previously reported 27,29 . Briefly, cell suspensions were incubated in Locke’s solution (154 mM NaCl, 5.6 mM KCl, 5.6 mM glucose, 2 mM CaCl 2 , 2 mM MgCl 2 , and 5 mM HEPES buffer adjusted to pH 7.4) supplemented with 3 μM Fura-2/AM for 50 min at 37 °C with continuous stirring.…”
Section: Methodsmentioning
confidence: 99%
“…SOCE is mediated by a series of factors, including TRPC1, Orai1, and STIM1 [ 41 ]. We have previously observed that thapsigargin-induced SOCE in PC12 cells is different from those in HL-60 cells and Jurkat T cells [ 42 ]. Therefore, we concluded that lipid rafts do not affect SOCE in salivary gland cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mAChRs, a series of GPCRs, including GPR39, histamine H 1 receptor, sphingosine–1–phosphate (S1P) receptor, bradykinin receptor, and P2Y 2 receptor (P2Y 2 R), has been investigated to identify salivary gland-related functions [ 52 , 58 , 59 , 60 , 61 ]. GPR39 is a type of GPCR with zinc as a ligand and is expressed in human SM gland tissues [ 52 ].…”
Section: Salivation By G-protein-coupled Receptor (Gpcr)-mediated Int...mentioning
confidence: 99%